Industry and academia partnership for aquatic renewable energy development in Colombia: A knowledge-education transfer model from the United Kingdom to Colombia. Issue 1 (1st January 2020) - Colmenares-Quintero, Ramon Fernando; Rojas, Natalia; Kerr, Sandy; Caicedo-Concha, Diana M.
Abstract: The need for "industry-academia knowledge transfer (IAKT)" and close collaboration in Colombia has been recognised as critical to innovation, while in the United Kingdom (UK) an IAKT model has been successfully deployed in the UK benefitting both stakeholders. As a result in Colombia, an IAKT model does not exist to guide these two key stakeholder groups. The methodology used is based on the analysis of the data collected directly from the aquatic renewable energy (ARE) industry and academia in the Orkney islands (Scotland). In addition, literature available in the public domain was used and analysed. Having this information, a knowledge-education model is proposed for the Colombian context. The IAKT model curriculum was based on ARE course topics and validated in a preliminary phase with UCC undergraduate engineering students from different disciplines. The results were very promising in terms of the skills developed by the students, not only technical but also in communication skills, teamwork, critical thinking and so on.